Subspace arrangements, BNS invariants, and pure symmetric outer automorphisms of right-angled Artin groups - Day, M; Wad, R (European Mathematical Society, 2018)
We introduce a homology theory for subspace arrangements, and use it to extract a new system of numerical invariants from the Bieri-Neumann-Strebel invariant of a group. We use these to characterize when the set of basis conjugating outer automorphisms (a.k.a. the pure symmetric outer automorphism group) of a right-angled Artin group is itself a right-angled Artin group.